2019
DOI: 10.3390/cancers11030404
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Signs in Glioma Pathology: Current Knowledge and Future Perspectives

Abstract: Historically restrained to immune defense against parasite infections, allergic inflammation has been recently rediscovered to protect from a wide array of environmental triggers, such as xenobiotics and carcinogens, which can induce DNA damage and ultimately lead to cancer development. Moreover, cells and mediators typical of allergic responses can importantly modulate the tissue inflammatory milieu, which represents a crucial gatekeeper towards the acquisition of malignancy by cancer cells through immune esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 55 publications
0
19
0
1
Order By: Relevance
“…Second, appropriately targeted allergic reactions are bene cial [25]. Allergic in ammation has been recently rediscovered to protect patients from a wide array of environmental triggers which can induce DNA damage and ultimately lead to cancer development, such as xenobiotics and carcinogens [26]. Third, antibiotic allergy was mediated by IgE [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, appropriately targeted allergic reactions are bene cial [25]. Allergic in ammation has been recently rediscovered to protect patients from a wide array of environmental triggers which can induce DNA damage and ultimately lead to cancer development, such as xenobiotics and carcinogens [26]. Third, antibiotic allergy was mediated by IgE [27].…”
Section: Discussionmentioning
confidence: 99%
“…Third, antibiotic allergy was mediated by IgE [27]. Theoretically, antigen-speci c IgE might promote direct tumor killing through antibody-dependent cell-mediated cytotoxicity [28], longer median survival period in glioma were associated with elevated serum IgE level [29] which was similar to the result in a mouse model of ovarian cancer [29,30]. Finally, excessive use of antibiotics may cause pathogenic bacteria to develop resistance and toxic reactions including neurotoxic reactions [31], whereas glioma patients with antibiotic allergy could avoid excessive use of antibiotics and the resulting damage.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have found that patients with atopic diseases including allergies, eczema, and asthma have a decreased susceptibility to grade II and III gliomas and improved prognosis 26 . It has been shown that there is an inverse relationship between serum IgE levels and risk of glioma, and high amounts of mast cells have been detected in GBM tissues 27,28 . Gohar et al .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on the allergic and nutritional epidemiology of glioma showed an inverse association between allergy and gliomas but did not provide any causal relationship between them [ 46 ]. The nutritional epidemiology studies suggested that various food groups and nutrients were associated with glioma risk; the results were inconclusive and not replicable in subsequent research [ 24 , 47 ].…”
Section: Epidemiology and Risk Factors Of Gliomamentioning
confidence: 99%